Cell death proteins in sepsis: key players and modern therapeutic approaches - Yang, Chloe S.; Coopersmith, Craig M.; Lyons, John D. (Frontiers in Immunology, 2024)
Cell death proteins play a central role in host immune signaling during sepsis. These interconnected mechanisms trigger cell demise via apoptosis, necroptosis, and pyroptosis while also driving inflammatory signaling. Targeting cell death mediators with novel therapies may correct the dysregulated inflammation seen during sepsis and improve outcomes for septic patients.